2017
DOI: 10.1007/s11011-017-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers of metabolic dysfunction is autism spectrum disorder: potential for biological diagnostic markers

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is behaviorally defined by social and communication impairments and restricted interests and repetitive behaviors. There is currently no biomarkers that can help in the diagnosis. Several studies suggest that mitochondrial dysfunction is commonly involved in ASD pathophysiology, but standard mitochondrial biomarkers are thought to be very variable. In the present study we examine a wide variety of plasma biomarkers of mitochondrial metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 88 publications
4
57
0
1
Order By: Relevance
“…These early observations were confirmed by our research group [20]. We previously recorded abnormal levels of the mitochondrial plasma markers pyruvate, lactate dehydrogenase, creatine kinase, glutathione-S-transferase (GST), caspase 7 and respiratory complex I (RCI) in children with ASD compared to those of age-and gender-matched control subjects.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…These early observations were confirmed by our research group [20]. We previously recorded abnormal levels of the mitochondrial plasma markers pyruvate, lactate dehydrogenase, creatine kinase, glutathione-S-transferase (GST), caspase 7 and respiratory complex I (RCI) in children with ASD compared to those of age-and gender-matched control subjects.…”
Section: Introductionsupporting
confidence: 56%
“…We previously recorded abnormal levels of the mitochondrial plasma markers pyruvate, lactate dehydrogenase, creatine kinase, glutathione-S-transferase (GST), caspase 7 and respiratory complex I (RCI) in children with ASD compared to those of age-and gender-matched control subjects. Moreover, our study demonstrated that most severely affected children had both RC I and GST abnormalities and that caspase 7, a marker of mitochondrial dysfunction, was the most discriminating biomarker between patients with ASDand controls [20].…”
Section: Introductionmentioning
confidence: 58%
“…The pathophysiological etiologies which precipitate autism symptoms remain elusive and controversial in many cases, but both genetic and environmental factors (and their interactions) have been implicated [25].…”
Section: Methodsmentioning
confidence: 99%
“…Some metabonomic studies have indicated the presence of elevated biomarkers in blood and urine samples from ASD patients, and these biomarkers include pyruvate, lactate, and mitochondrial-related enzymes [12][13][14]. Major analytical techniques for metabolomics are nuclear magnetic resonance spectroscopy (NMR) and chromatography, including gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS).…”
Section: Introductionmentioning
confidence: 99%